2003
DOI: 10.1177/021849230301100111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Renal Dysfunction on Cardiac Surgery Results

Abstract: Results of cardiac surgery were analyzed using a database that included plasma creatinine levels in 2,214 patients, of whom 507 had preoperative renal dysfunction (creatinine clearance < 0.9 mL x s(-1) x m(-2)). Logistic regression and propensity score analyses found preoperative renal dysfunction to be an independent predictor of morbidity and mortality. Plotting preoperative creatinine clearance against morbidity and mortality revealed an exponential increase in morbidity and mortality when preoperative crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
4
2
Order By: Relevance
“…Although it is well established that preoperative renal insufficiency increases mortality in patients undergoing cardiac surgery, 19,20 in this investigation baseline renal function was not associated with outcome. A proportion of patients with renal dysfunction on VAE received renal replacement therapy at the same time.…”
Section: Outcome After Extracorporeal Membrane Oxygenationcontrasting
confidence: 55%
“…Although it is well established that preoperative renal insufficiency increases mortality in patients undergoing cardiac surgery, 19,20 in this investigation baseline renal function was not associated with outcome. A proportion of patients with renal dysfunction on VAE received renal replacement therapy at the same time.…”
Section: Outcome After Extracorporeal Membrane Oxygenationcontrasting
confidence: 55%
“…The authors also concurred with the previous investigators that the length of hospital stay was prolonged in renal insufficiency patients compared with patients with normal renal function (p = 0.0006) [3,7,9] . However, this study differed from others in that the incidence of complications in terms of gastrointestinal bleeding, reoperation for bleeding, respiratory failure, wound infection, perioperative myocardial infarction, stroke and 30-day mortality rates was comparable between the groups of patients with normal and abnormal renal functions, while several other studies showed an increased incidence of these complications among patients with renal insufficiency [3,9,10] . The authors attributed the improved outcomes in their study to the effective perioperative management by avoiding hypotension, fluid and potassium overloading, withdraw of angiotensin-converting enzyme inhibitors 24 h prior to the surgery and limiting CPB time.…”
contrasting
confidence: 85%
“…In stages 1–4, there was increase in bleed requiring reoperation of 1.3%, 3.0%, 5.7% and 8.3%, respectively, and increase in total complications of 3.5% (n = 8), 6.3% (n = 36), 10.9% (n = 25) and 12.5% (n = 3), respectively (fig. 3) [12], but this was not statistically significant. Thirty-day mortality occurred in 5 of 1,052 patients (0.47%) with no statistical difference in stages 1–4 [0.43% (n = 1), 0.35% (n = 2), 0.86% (n = 2) and 0.0% (n = 0), respectively].…”
Section: Resultsmentioning
confidence: 99%